PENGARUH PENERAPAN MODEL TPS (THINK PAIR SHARE) TERHADAP MINAT BELAJAR SISWA KELAS VII PADA MATA PELAJARAN BIOLOGI DI MTs NEGERI 1 PALEMBANG - Leny Marlina; Ummi Hiras Habisukan; Devy Arfika (Program Studi Pendidikan Biologi Fakultas Ilmu Tarbiyah dan Keguruan Universitas Islam Negeri Raden Fatah Palembang, 2017)
TPS (think pair share) commonly called the methods of teaching and learning to think, pair,and share. This model gives students the opportunity to learn and work independently of eachother. Models TPS (think pair share) has three steps, namely think, pair, and share. Each ofthe steps have a strategy that will allow the students to learn. The aim of the study was todetermine the effect of Think Pair Share toward student’ s learning interest result on thebiological at grade VII of MTs Negeri 1 Palembang for academic years on 2016/2017. Themethod was true experimental design with Posttest-Only Control Design type. The populationin this research were all students of seventh grade of MTs Negeri 1 Palembang on 2016/2017academic year. The sample was taken by using Cluster Random sampling. The sample wasstudents as experiment class at grade VIIC and students as a control class at grade VIIB. Theinstrument of the study was the questionairre. The data analysis used t-test, and obtained ttest= 2,922 of significant 0,05 that ttable = 1,667, so it can be concluded that by t-test> t-tablemeans that alternative hypothesis was accepted. Based on the results of this study concludedthat the learning model TPS (think pair share) increase interest in studying biology on thetopic of the interaction of living things and the environment in the seventh grade students ofMTs Negeri 1 Palembang in Academic Year 2016/2017